Population dynamics of Sardinella jussieui (Valenciennes, 1847) in the Gulf of Suez, Egypt - Mehanna, Sahar F; El-Ganainy, Azza A (Indian Journal of Fisheries, 2011)
Age, growth, mortality and yield per recruit of Sardinella jussieui collected from the Gulf of Suez during October 2000-May 2001 have been estimated from the length-frequency distribution data. Growth is well described by von Bertalanffy equation (Lt= 24.78 (l-e-0.65(t+0.33)). The annual rates of total, natural and fishing mortality were calculated as 1.31, 0.32 and 0.99 respectively. Exploitationrate E was estimated as 0.76. The relative yield per recruit analysis shows that the stock of S. jussieui is overexploited and the fishing mortality rate must be reduced